1993
DOI: 10.1128/jb.175.10.2809-2817.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a segment of the Escherichia coli Tsx protein that functions as a bacteriophage receptor area

Abstract: The Escherichia coli outer membrane protein Tsx functions as a nucleoside-specific channel and serves as the receptor for colicin K and a number of T-even-type bacteriophages, including phage T6. To identify those segments of the Tsx protein that are important for its phage receptor function, we devised a selection and screening procedure which allowed us to isolate phage-resistant strains synthesizing normal amounts of Tsx.Three different Tsx-specific phages (T6, Oxi, and H3) were employed for the selection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…ictaluri phage susceptibility. These results showed striking similarities with a previous finding that demonstrated that alterations clustered in a small region near the surface-exposed carboxy terminus of Tsx protein resulted in Tsx-specific phage-resistance phenotypes (Schneider et al, 1993). The involvement of other surface-exposed regions in phage attachment is not unexpected as it has been demonstrated by mutational analysis of several phage receptors (Cole et al, 1983;Gehring et al, 1987;Heine et al, 1988).…”
Section: Discussionsupporting
confidence: 78%
“…ictaluri phage susceptibility. These results showed striking similarities with a previous finding that demonstrated that alterations clustered in a small region near the surface-exposed carboxy terminus of Tsx protein resulted in Tsx-specific phage-resistance phenotypes (Schneider et al, 1993). The involvement of other surface-exposed regions in phage attachment is not unexpected as it has been demonstrated by mutational analysis of several phage receptors (Cole et al, 1983;Gehring et al, 1987;Heine et al, 1988).…”
Section: Discussionsupporting
confidence: 78%
“…OmpF has been known to comigrate with OmpC on SDS-PAGE gels (5,37). We performed Western blotting analysis to ascertain that the changes in cellular OmpC concentration can be reflected by the fluctuating intensity of the 33-kDa protein band.…”
Section: Ar1-resistant Mutants Obtained By Transposon Mutagenesismentioning
confidence: 99%
“…For example, phages Mu (84) and X174 (41) initially bind to lipopolysaccharide, whereas (95), T6 (86), and TLS (30) adsorb to the OM proteins LamB, Tsx, and TolC, respectively. T2 (53) and T4 (92,102) utilize both lipopolysaccharide and surface proteins in their adsorption reactions.…”
mentioning
confidence: 99%